Analysis of the political process of Denmark's hospital reform. (30th September 2020) - Reichebner, C; Berger, E; Eriksen, A
Abstract: Background: The German hospital landscape is characterized by a decentralization of the range of services provided, low levels of specialization and significant overcapacity. This leads to over-, under- and misuse of hospital care, which is not least evidenced by wide variation in quality in the system. In Denmark, since the early 2000s, a continuous restructuring of the hospital landscape has been undertaken. Among other things, hospitals have been rebuilt, many smaller hospitals have closed and the number of emergency rooms has been halved. The aim of the project K:IDD (Hospital: Impulses for Germany from Denmark) is to examine the conditions that have to be created to be able to incorporate parts of the Danish reform into German hospital care, and to leverage these for improved patient care. To learn from the case of Denmark, it is important to understand which circumstances facilitated the reform. Methods: To analyse the political process behind Denmark's hospital reform using two different sources will be used: (1) A qualitative content analysis of 17 semi-structured expert interviews with political scientists, journalists, politicians, among others and (2) an analysis of the literature about the reform. Kingdon's (1994) multiple stream framework as well as Tsebelis' (1995) Veto-player theory will be used. Results: The key success factors encouraging to the reform will be presented. In addition potential Veto-Players and institutional settings enabling or hindering the reform will be described. The final assessment of the policy process and comparison to the German context will lead to implementation guidance and recommendations for the German context. Further, alternative courses of action will be presented. Conclusions: The findings from this analysis can provide important and practical recommendations for the necessary reform of the hospital landscape in Germany, thereby improving hospital care in the long term. Key messages: The hospital reform in Denmark was possible due to the interaction of different social currents, which ultimately opened a window of opportunity. This could be used as role model for decision-makers, professionals and researchers strive for change in other countries.